A Model for Production-Distribution Networks with Transit Billing - Meyer, Carl F. (Management Science, 1967)
The model presented in this paper uses the method of linear programming to solve multi-plant, multi-product distribution networks constrained by plant production schedules and manufacturing combinations when the shipment of final goods is a function of the raw material input. This function connecting inbound material with outbound finished goods at a given production facility is described by the privilege of mill-in-transit granted by the material haulers. The model is developed under very general assumptions, and is able to solve the networks in terms of optimally applying transit billing, determining production schedules and combinations, and final distribution of product to customer while allowing for outside purchases of the same end products.